Study of the Variability of the Chemical Profile, and Biological Activity Approaches of Hedychium coronarium J. Koenig Essential Oil from Different Habitats of Uttarakhand, India - Sushila Arya; Sonu Kumar Mahawer; Himani Karakoti; Ravendra Kumar; Om Prakash; Satya Kumar; Mamta Latwal; Ganesh Panday; Ravi Mohan Srivastava; Mozaniel Santana de Oliveira; Dharmendra Singh Rawat (Journal of Food Quality)
The objective of the current study was to evaluate the altitudinal variability in chemical compounds, nematicidal, insecticidal, herbicidal, and antifungal activity of the essential oils of H. coronarium collected from four different habitats of Tarai and Kumaun region of Uttarakhand. Essential oils were hydro-distilled from rhizomes of H. coronarium, and their yield varied from 0.05 to 0.25% (v/w). Based on GC-MS analysis, the major compounds observed were 1, 8-cineole (12.21–18.27%), coronarin E (10.20–14%), α-terpineol (5.32–10.13%), terpinen-4-ol (2.20–4.67%), α-pinene (4.90–8.77%), Z-caryophyllene (4.67–12.29%), and linalool (1.96–4.62%). To visually observe the variation in the oil composition profile of essential oils, heat map clustering, Venn diagram, and principal component analysis (PCA) were performed. To evaluate the pesticidal properties, the essential oils were tested under laboratory conditions. Additionally, significant nematicidal activity was demonstrated by essential oils against Meloidogyne incognita, good insecticidal activity against Spodoptera litura, and moderate herbicidal activity on Raphanus raphanistrum subsp. sativus, and effective antifungal activity against Fusarium oxysporum and Curvularia lunata was observed in the current investigation.